EFFECT OF FORCE MOLTING BY ZINC OXIDE AND THE ROLE OF VITAMIN C ON BODY WEIGHT AND REENTRY TO PRODUCTION OF BROILER BREEDER - Shahla M.S. Al-Kirkuki (Mesopotamia Journal of Agriculture)
A total of 296 Arbor Acres broiler breeder 375 days old were randomly divided into eight treatment. Hens in each treatment were subdivided into five replicates and reared on the floor throughout the experimental period. Two treatments free of Zinc included control with or without vitamin C; six treatments included three levels of Zn as ZnO (15000, 20000 and 25000ppm) with or without vitamin C. All treatments extirpated significant differences in percentage body weight loss during molting program. The most significant loss occurred in the T8 and T7 hens. The most reduction of feed intake (%) occurred in T8, T7 and T6 respectively. Furthermore, molting periods significantly affect body weight loss and feed intake (%). The most significant loss of body weight and reduction of feed intake (%) were occurred at day 9 of molting period. Moreover, T4 hens significantly take up more days to 1st day out of production, less days to out of production and to return to egg production compared with other molting treatments